1997
DOI: 10.1097/00003072-199709000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tc-99m Bone Imaging in the Management of Pain After Complicated Total Hip Replacement

Abstract: A case of reflex sympathetic dystrophy (RSD) after total hip replacement (THR) is reported. It is a very unusual cause of pain after any arthroplasty procedure. Three-phase bone imaging diagnosed the condition and sympathetic blockade was used for confirming and treating the condition. The role of the bone scan in differentiating RSD from other causes of pain after THR is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Since its first description in 1916 [ 10 ], CRPS has been rarely described after hip surgery and can easily be ignored by the inexperienced physician [ 4 , 5 , 11 ]. Patman et al [ 12 ] reported 113 cases of post-traumatic pain syndrome of which only 18 had their diagnosis made by the treating physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its first description in 1916 [ 10 ], CRPS has been rarely described after hip surgery and can easily be ignored by the inexperienced physician [ 4 , 5 , 11 ]. Patman et al [ 12 ] reported 113 cases of post-traumatic pain syndrome of which only 18 had their diagnosis made by the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally related to painful conservative or surgical distal radius fracture treatment, under the term of “Sudeck syndrome” [ 3 ]. To our knowledge, there is a paucity of literature reporting this syndrome after THR, since only two case reports have been published [ 4 , 5 ]. We thenceforth describe the clinical outcome of three cases of CRPS developed after elective THR, which share similarities and differences with the cases already reported.…”
Section: Introductionmentioning
confidence: 99%
“…Increased uptake is seen in aseptic loosening, infection, heterotopic bone formation, stress fractures, tumours, metabolic bone disease, and reflex sympathetic dystrophy. 34 However, increased uptake is seen for up to two years after uncomplicated THR, 35 which reduces the value of this investigation in evaluating suspected loosening or infection in its early stages. In a series of 54 patients with painful hip arthroplasties who had surgical exploration, Lieberman et al 36 reported that technetium bone scanning had a lower sensitivity and specificity than serial plain radiographs for diagnosing femoral and acetabular component loosening and they recommended using bone scanning only when plain radiography was inconclusive.…”
Section: Investigationmentioning
confidence: 99%
“…It is also reported following crush injury to the foot, 22 ankle arthrodesis, 23 amputation 24 and hip arthroplasty. 25 It is well-described following minor interventions such as arthroscopy, in which there is only minimal trauma. 26,27 One multi-centre study quotes a frequency of 2.3% following knee arthroscopy.…”
Section: What Triggers Rsd?mentioning
confidence: 99%